Composition of the aquatic invertebrate fauna associated to the mangrove vegetation of a coastal river, analyzed through a manipulative experiment - Corrêa, Michéle De Oliveira Dias Alves [UNESP]; Uieda, Virgínia Sanches [UNESP] (My University, 2008)
The present study analyzed the composition of the aquatic fauna associated to the mangrove forest in a southeastern Brazilian river. The composition of the macrofauna in the roots of the marginal vegetation located at three different salinity stretches was analyzed by sampling pieces of the submerged branches of the vegetation (natural substrate) and pieces of sisal rope (artificial substrate), installed close to the natural vegetation and sampled after a period of 14 colonization days. In both types of substrate, twelve taxonomic groups were sampled, representing three phyla (Cnidaria, Annelida and Arthropoda). The crustaceans, corresponding to the most diversified group, were represented by Copepoda, Tanaidacea, Isopoda, Amphipoda and Decapoda. The highest salinity stretch showed the highest abundance, with a progressive decrease from high to low salinity for both substrates. Copepoda and Tanaidacea predominated on both substrates, although the artificial substrate exhibited the highest total abundance and species richness. Considering the relative abundance of the taxonomic groups on both substrates, the majority of groups predominated in the highest salinity range. Significant differences on the longitudinal distribution of abundance were associated to the variation on salinity and with the complexity of the substrate.
Keywords: Artificial substrate; Colonization; Macroinvertebrates; Natural substrate; Salinity stretches